The association of Toxoplasma gondii IgG and cognitive function scores: NHANES 2013–2014. (October 2020) - Wiener, R. Constance; Waters, Christopher; Bhandari, Ruchi
Abstract: Toxoplasma gondii ( T. gondii ) causes chronic, latent infections of global concern. Its subclinical influence on behavior and cognition are poorly understood. The objective of this research is to determine the relationship of T. gondii IgG with cognition using National Health and Nutrition Examination Survey data, 2013–2014 in older adults ≥60 years. A composite cognitive function score was created by adding the scores of the memory test, language/verbal fluency, and working memory test. T. gondii IgG was dichotomized at <33 IU/mL (negative) and ≥33 IU/mL (positive). There were 19.2% of the participants who were T. gondii IgG + . The memory function and language/verbal fluency subtests failed to reach significance; however, the difference in the working memory test was significant. In the multivariable ordinal logistic regression analysis, controlling for potential confounders, the odds of cognitive function scores decreasing in quartiles among people with positive vs. negative T. gondii IgG are 1.55 (95% CI: 1.08, 2.21; p = .0170). Establishing an evidence base for the association of T. gondii IgG and cognition is complex, but essential. Graphical abstract: Blue-12.8% positive for Toxoplasmosis gondii IgG and below mean composite function score. Yellow-37.7% negative for Toxoplasmosis gondii IgG and below mean composite function score. Purple-8.2% positive for Toxoplasmosis gondii IgG and above mean composite function score. Gray-41.3% negative for Toxoplasmosis gondii IgG and above mean composite function score. Icon arrays generated using code made available by http://www.iconarry.com Risk Science Center and Center for Bioethics and Social Sciences in Medicine, University of Michigan. Accessed 2020-02-05. Icon array code is freely available on GitHub under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License. Unlabelled Image Highlights: Association of cognitive function decline and T. gondii IgG + 80.8% negative for T. gondii IgG Association of working memory decline and T. gondii IgG + Memory function and T. gondii IgG + failed to reach significance. Language/verbal fluency and T. gondii IgG + failed to reach significance.